Stability analysis for traits related to water use efficiency in sunflower (Helianthus annuus L.): STABILITY ANALYSIS FOR TRAITS RELATED TO WATER USE EFFICIENCY IN SUNFLOWER - PRAFULL KUMAR; S K DHILLON; ABHINAV SAO (Journal of Oilseeds Research, 2014)
The present study was conducted to evaluate the stability of 41 genotypes with respect to various morphophysiological traits affecting water use efficiency in sunflower. The four water stress environments were created by skipping irrigation at different plant growth stages. The data were recorded for canopy temperature (°C), photosynthetic capacity, leaf area index, leaf water potential (mpa), days to 50% flowering, days to maturity, plant height (cm), head diameter (cm), 100-seed weight (g), seed yield/plant (g) and oil content (%). The analysis of variance revealed that the genotypes and environment (linear) showed significant interaction for all the traits under study which indicated that phenotypic expression of all the genotypes for these characters was influenced significantly by environments. The pooled deviations for all the characters were significant indicating that the performance of genotypes varied in different environments. The phenotypic stability of genotypes was measured by three parameters namely mean performance over environments, regression coefficient and deviation from regression line. The genotypes viz., P112R, NDLR1 and 7-1-B for days to 50% flowering ; P107RP2, P112R, 304B and 52B for days to maturity; P93R, P69R and P115R for seed yield/plant; P124R and 45B for 100-seed weight and P93R, 95C1R and P91R for oil content showed stable performance over different water stress environments. None of the genotypes was found stable for plant height.